Investigations on skeletal growth zones via bone scans as base of determination of optimal time for surgery in mandibular asymmetry - Reuland, P.; Werz, R. (Nuklearmedizin - NuclearMedicine, 2000)
Aim of the study was to find out wether there is a common stop of growth of mandibular bone, so that no individual determination of the optimal time for surgery in patients with asymmetric mandibular bone growth is needed. As there are no epiphyseal plates in the mandibular bone, stop of growth cannot be determined on X-ray films. Methods: Bone scans of 731 patients [687 patients (324 male, 363 female) under 39 y for exact determination of end of growth and 44 (21 male, 23 female) patients over 40 y for evaluation of nongrowth dependant differences in tracer uptake] were reviewed for the study. All the patients were examined 3 hours after injection of 99mTc-DPD. Tracer uptake was measured by region of interest technique in different points of the mandibular bone and in several epiphyseal plates of extremities. Results: Tracer uptake in different epiphyseal plates of the extremities shows strong variation with age and good correlation with reported data of bone growth and closure of the epiphyseal plates. The relative maximum of bone activity is smaller in mandibular bone than in epiphyseal plates, which show well defined peaks, ending at 15-18 years in females and at 18-21 years in males. In contrast, mandibular bone shows no well defined end of growing but a gradually reduction of bone activity which remains higher than bone activity in epiphyseal plates over several years. Conclusion: No well defined end of growth of mandibular bone exists. The optimal age for surgery of asymmetric mandibular bone growth is not before the middle of the third decade of life, bone scans performed earlier for determination of bone growth can be omitted. Bone scans performed at the middle of the third decade of life help to optimize the time of surgical intervention.
Keywords: Mandibular asymmetry; surgery; scintimetric evaluation of growth zones; pediatry